2012
DOI: 10.1086/664698
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Energy Stores and Stroke Rates of Emperor Penguins: Implications for Muscle Metabolism and Dive Performance

Abstract: In diving birds and mammals, bradycardia and peripheral vasoconstriction potentially isolate muscle from the circulation. During complete ischemia, ATP production is dependent on the size of the myoglobin oxygen (O2) store and the concentrations of phosphocreatine (PCr) and glycogen (Gly). Therefore, we measured PCr and Gly concentrations in the primary underwater locomotory muscle of emperor penguin and modeled the depletion of muscle O2 and those energy stores under conditions of complete ischemia and a prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Although such buoyancies, especially for king and emperor penguins, are higher than typically estimated for small penguins, buoyancy is greater in larger animals (Miller et al, 2004;Skrovan et al, 1999), and emperor and king penguins are much larger birds than those other avian species in which buoyancy has been previously estimated. In addition, greater buoyancy could probably be rapidly diminished by a quicker descent and faster stroke rate at the start of deeper dives (Williams et al, 2012). Lastly, field observations of floating penguins (Fig.…”
Section: Body Density and Buoyancymentioning
confidence: 95%
“…Although such buoyancies, especially for king and emperor penguins, are higher than typically estimated for small penguins, buoyancy is greater in larger animals (Miller et al, 2004;Skrovan et al, 1999), and emperor and king penguins are much larger birds than those other avian species in which buoyancy has been previously estimated. In addition, greater buoyancy could probably be rapidly diminished by a quicker descent and faster stroke rate at the start of deeper dives (Williams et al, 2012). Lastly, field observations of floating penguins (Fig.…”
Section: Body Density and Buoyancymentioning
confidence: 95%
“…ATP concentrations within red and white skeletal muscle fibers from vertebrates (see Refs. 6,11,27,36,56,72,119,146,157,160,164,177,182,200,202,207,219,243,256,265,269,293,294,308). For mammals, red vs. white [CP], P = 0.0006 (two-tailed t test); for all vertebrates combined, red versus white [CP], P = 0.0085 (two-tailed t test).…”
Section: Sources Of Energy That Power Metabolismmentioning
confidence: 99%
“…A longer recovery period at the surface might also have been the consequence of an increased contribution of anaerobic metabolism (especially phosphocreatine, PCr) during diving. While reliance on anaerobic metabolism might be limited to extended dives (Baldwin et al, 1984;Baldwin, 1988;Ponganis et al, 1997d), PCr recovery might be similarly fast as Mb-O 2 recovery (Williams et al, 2012). For emperor penguins, which possess a large anaerobic energy reserve in form of glycogen and PCr in their pectoral muscles, it was suggested that Mb-O 2 and PCr recovery should occur within most observed post-dive surface intervals (Williams et al, 2012).…”
Section: Dive/foraging Effort During Pre-and Post-molt Tripsmentioning
confidence: 99%
“…While reliance on anaerobic metabolism might be limited to extended dives (Baldwin et al, 1984;Baldwin, 1988;Ponganis et al, 1997d), PCr recovery might be similarly fast as Mb-O 2 recovery (Williams et al, 2012). For emperor penguins, which possess a large anaerobic energy reserve in form of glycogen and PCr in their pectoral muscles, it was suggested that Mb-O 2 and PCr recovery should occur within most observed post-dive surface intervals (Williams et al, 2012). A stronger depletion of the reduced oxygen stores during post-molt (and/or a potential increase in anaerobic metabolism) could be the consequence of an increased work load to generate sufficient heat so that the presumably high heat loss can be balanced and core temperature is maintained (see discussion on vertical speed changes below).…”
Section: Dive/foraging Effort During Pre-and Post-molt Tripsmentioning
confidence: 99%
See 1 more Smart Citation